The human factors of the national economic development: a comparative analysis of Poland and Ukraine - Kubiniy, Natalya; Zavadyak, Roman; Hudzovata, Liudmyla (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/020, 2021)
A comparative assessment of the level of economic progress and indicators of human development in Poland and Ukraine as interconnected and at the same time strategic factors in building a competitive national economy has been carried out. The range of factors related to human development and the use of the country's labor potential, affecting the competitiveness of the national economy as a result of economic development, has been determined. These factors include: labor productivity, reflecting managerial, economic, institutional potential of competitiveness; educational turnover in the country, which characterizes the ability of the labor market to accept highly qualified specialists; the level of educational load on the population, which indicates the readiness and intentions of the country and its labor potential to move to the knowledge economy. A statistical model for determining the influence of these factors on the discrepancy between the levels of economic development of Poland and Ukraine has been built; using a statistical model, the influence of these factors was determined. The performed calculations of the influence of the factors of the role of freedom were to determine the reasons for Ukraine’s lag behind Poland, concerning human development. The ways of increasing the rates of economic development of Ukraine on the basis of increasing material incentives, increasing costs for education, increasing educational burden on the population, using the mechanism of intentions are proposed.